Если \(a=12, b=9\), а также \(c=4\), что такое \((b^2-2c^2)/(a+c-b)\)?

0
0

Если \(a=12, b=9\), а также \(c=4\), что такое \((b^2-2c^2)/(a+c-b)\)?

0
0

Смотрите процесс решения ниже:

Объяснение:

Замена: \[(12)\] для каждого случая \[(a)\] \[(9)\] для каждого случая \[(b)\] \[(4)\] для каждого случая \[(c)\] а затем рассчитать результат: \[((b)^2 — 2(c)^2)/((a) + (c) — (b))\] будет выглядеть так: \[((9)^2 — (2 * (4)^2))/((12) + (4) — (9)) =>\] \[(81 — (2 * 16))/(16 — (9)) =>\] \[(81 — 32)/7 =>\] \[49/7 =>\] \[7\]

Показан 1 результат